JALAN BERMAKNA PEMECAHAN MASALAH: MENGELOLA FAKTOR PENENTU IMPLEMENTASI KEBIJAKAN TRANS METRO BANDUNG DI KOTA BANDUNG PROVINSI JAWA BARAT - Lestari, Sandrina Fuji Indah; Hamdi, Muchlis; Rahmah, Mutia (Jurnal Ilmiah Wahana Bhakti Praja, 2024)
. Congestion is one of the problems that occur in urban areas, one of which is the city of Bandung. To overcome this problem, the Bandung City Government has established a policy on Trans Metro Bandung with the aim of improving services and providing integrated, safe, fast, smooth, orderly, regular, comfortable, reliable and efficient public transportation. But the policy has not been able to achieve the set goals. This study aims to analyze the determinants and efforts to optimize the success of Trans Metro Bandung policy implementation in Bandung City. This research uses a postpositivist approach with data collection techniques in the form of interviews, observation, and documentation. The informant determination technique used is purposive sampling and snowball sampling. Data analysis used is collection, condensation, presentation, and conclusion drawing. The results showed that there were factors that hindered the implementation of the Trans Metro Bandung policy, namely the difficulty of implementing policy instruments, unclear policy design related to resources and target changes, insufficient resources needed, inability to implement SOPs, and the low level of benefits felt by the community. The results of this study also show that there are supporting factors for the implementation of the Trans Metro Bandung policy, namely the appropriate policy instruments, the existence of a supervisory structure, the appropriate institutional design, the adequacy of the resources needed, and the involvement of the community. Efforts that need to be made to optimize the Implementation of Trans Metro Bandung Policy in Bandung City are to integrate mass transportation that connects Greater Bandung, improve the quality of Trans Metro Bandung services, and recruit competent information management human resources and appropriate promotion of Trans Metro Bandung services. Keywords: Implementation Policy, Transportation Policy, Trans Metro Bandung